PERAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN KOMITMEN GURU DI SEKOLAH GRACIA ABADI, TANGERANG [THE ROLE OF TRANSFORMATIONAL LEADERSHIP ON TEACHERS' COMMITMENT AT GRACIA ABADI TANGERANG SCHOOL] - Song Eun Mi (Jurnal Ketopong Pendidikan, 2021)
Some teachers and staffs at Gracia Abadi Tangerang School have been working together to build a school building without receiving a salary. It is so rare today that the researcher became very interested in researching this further while thinking that the leadership of school’s founder has had a positive impact on teachers. This study aims to know: 1) how the school founder applies transformational leadership in school management, 2) what are the impacts and constraints experienced in applying transformational leadership, 3) the impact of transformational leadership on teacher commitment at this school. This study uses qualitative phenomenological methods with data collection techniques using in-depth interviews, observation, and document review. The validity of the data will be tested with source triangulation. The results of this research indicate that transformational leadership has been shown to have a positive impact on teacher commitment in Gracia Abadi School.